سائنسی تفسیر کے قائلین ومانعین کے دلائل کا تجزیہ اور موقف اعتدال: Analysis and moderation of the arguments of the proponents and opponents of scientific interpretation - Asghar Ali Khan, Dr; Dr. Zahoor Ullah Al Azhari, Prof. (International Research Journal of Arabic and Islamic Studies, 2023)
The Holy Qur’an has the status of the last book in terms of descent among all the heavenly books. The creator of the universe has placed such mysteries and knowledge gems in it that no one can claim to find them all completely till the hereafter day. The Holy Qur’an is the intellectual miracle of the Last Prophets and Messengers. It is a humbling book in science and language. There is no difference in this book in describing the news of the past and the present. It is such a miracle that the knowledge of academic matters, religious issues, political & economic rules, collective details, human rights and human order is contained in itself. Truthfulness is the world’s remaining argument on Islam, since this book was revealed. Since then it has been worked on in various dimensions, but the research avenues are still open for researchers and scholars. Rather, there are many aspects that have not been fully explored. Scholarly research has so far unable to produce such an astonishing book. This research will try to provide a moderate way to go ahead positively in research for the betterment and reformation of society